EFL Students’ Attitudes toward Public Speaking and Anxiety in Speaking Impromptu Speech - Imron, Ali; Hantari, Winda Candra (Fakultas Ilmu Budaya, Universitas Mulawarman, 2019)
This study aims to examine students’ attitudes towards public speaking class and the possible causes that lead them to have anxiety in performing impromptu speech. A qualitative research design employing the in-depth semi-structured interview has been carried out with 23 students of Tidar Islamic Boarding School in Magelang, Central Java. The study involves a public speaking class consisting of 8 male students and 15 female students. The Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire was also given to the students to measure the level of their anxiety in performing impromptu speech. The findings show that the students have positive attitudes towards public speaking class. Meanwhile, the possible cause of anxiety are because they are not accustomed to speak in English, especially in front of many people, and the lack of vocabularies and confidence. Penelitian ini bertujuan untuk mengetahui perspektif siswa terhadap kelas public speaking dan beberapa faktor yang dapat menyebabkan siswa mengalami kesulitan saat melakukan pidato dengan metode impromtu. Desain penelitian kualitatif dan menggunakan wawancara semi-terstruktur telah dilakukan dengan melibatkan 23 siswa Pondok Pesantren Tidar di Magelang, Jawa Tengah. Penelitian ini melibatkan siswa yang tergabung dalam kelas public speaking dan terdiri dari 8 siswa laki-laki, serta 15 siswa perempuan. The Foreign Language Classroom Anxiety Scale (FLCAS) digunakan dalam penelitian ini untuk mengukur tingkat kecemasan siswa saat melakukan pidato dengan metode impromtu. Hasil penelitian ini menunjukkan bahwa siswa memiliki sikap positif terhadap kelas public speaking. Sementara itu, kemungkinan penyebab kecemasan mereka adalah karena tidak terbiasa berbicara dalam bahasa Inggris dengan jumlah audience yang banyak, juga kurangnya kosa kata dan rasa percaya diri.